Wheat harvester convoys spatiotemporal patterns mining using a recursive search-based DBSCAN algorithm - Zhai, Weixin; Han, Ruijing; Pan, Jiawen; Wu, Caicong (International Journal of Agricultural and Biological Engineering, 2025)
Due to varying crop maturity periods and uneven distribution of agricultural machinery, China has developed a unique service model known as cross-regional agricultural machinery operations. Currently, China’s comprehensive mechanization rate for grain crops is relatively high, creating a substantial market for cross-regional agricultural machinery operations. Research on the behavioral patterns of cross-regional agricultural machinery migration is both urgent and significant. Considering the actual rules of cross-regional migration during the wheat harvest and the characteristics of the trajectory data, this paper proposes a trajectory mining method using a recursive search-based DBSCAN (Density-Based Spatial Clustering of Applications with Noise) algorithm. One representative finding of this study is that by mining the trajectory data of wheat harvesters within 25 d of peak harvest period, 131 cross-regional trajectories were identified, consisting of 11 633 harvesters. Three main routes of wheat harvester cross-regional migration were identified, along with several smaller routes outside their range. The overall spatiotemporal pattern aligns with observed realities in China. This study can provide valuable references for operators to optimize cross-regional routes, for agricultural machinery manufacturers to develop location-based services, and for relevant government departments to formulate policies. Key words: trajectory data mining; cross-regional convoy; cross-regional agricultural machinery operations; wheat harvester; spatiotemporal patterns DOI: 10.25165/j.ijabe.20251806.9793 Citation: Zhai W X, Han R J, Pan J W, Wu C C. Wheat harvester convoys spatiotemporal patterns mining using a recursive search-based DBSCAN algorithm. Int J Agric & Biol Eng, 2025; 18(6): 221–229.